Effect of heating temperature on tritium retention in stainless steel type 316 L. (August 2018) - Matsuyama, M.; Zushi, H.; Tokunaga, K.; Kuzmin, A.; Hanada, K.
Highlights: Effects of heating temperature on tritium retention behaviur have been studied using SS316L samples as a model. Tritium retention behaviur strongly depended on degassing temperature as well as tritium exposure temperature. Significant increase in tritium retention appeared in a degassing temperature region above 573 K. Tritium retention behaviur in the plasma-exposed sample was similar to that in the plasma non-exposed samples. Changes in chemical states of sample surface with heating were consistent with the tritium retention behaviur. Abstract: Dependence of heating temperature on tritium retention behavior in stainless steel type 316 L (SS316L) has been examined about each process of degassing and tritium exposure. Two kinds of SS316L samples were employed: bare SS316L and plasma-exposed SS316L. The amount of tritium retained in surface layers of a sample was nondestructively measured by β-ray-induced X-ray spectrometry, and changes in the surface state with heating in vacuum were analyzed by X-ray photoelectron spectroscopy (XPS). Significant increase in tritium retention in bare SS316L samples appeared in a degassing temperature region above 600 K. Similar tendency of tritium retention was observed for the plasma-exposed sample. It was seen that the degassing process prior to tritium exposure significantly influenced to the tritium retention behavior. Furthermore, it was suggested from surface analysis by XPS that chemical states of SS316L surface at high temperatures play an important role for tritium retention behavior.